2014
DOI: 10.3171/2013.10.spine12944
|View full text |Cite
|
Sign up to set email alerts
|

A new alarm point of transcranial electrical stimulation motor evoked potentials for intraoperative spinal cord monitoring: a prospective multicenter study from the Spinal Cord Monitoring Working Group of the Japanese Society for Spine Surgery and Related Research

Abstract: Object Although multimodal intraoperative spinal cord monitoring provides greater accuracy, transcranial electrical stimulation motor evoked potential (TcMEP) monitoring became the gold standard for intraoperative spinal cord monitoring. However, there is no definite alarm point for TcMEPs because a multicenter study is lacking. Thus, based on their experience with 48 true-positive cases (that is, a decrease in potentials followed by a new neurological motor deficit postoperatively) encountered between 2007 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 16 publications
3
103
0
Order By: Relevance
“…An overly conservative (specific) MEP alert criterion may not be sufficiently sensitive during some cranial and spinal surgeries. In this instance, an opportunity to intervene may be missed and a new postoperative deficit may result (Zhou and Kelly, 2001;Dong et al, 2005;Kobayashi et al, 2014). On the other hand, an overly sensitive criterion for some procedures could produce too many false alarms and compromise surgical treatment, resulting in incomplete tumor removal or suboptimal deformity correction.…”
Section: Utilization: In What Context Are Eps Used?mentioning
confidence: 94%
See 2 more Smart Citations
“…An overly conservative (specific) MEP alert criterion may not be sufficiently sensitive during some cranial and spinal surgeries. In this instance, an opportunity to intervene may be missed and a new postoperative deficit may result (Zhou and Kelly, 2001;Dong et al, 2005;Kobayashi et al, 2014). On the other hand, an overly sensitive criterion for some procedures could produce too many false alarms and compromise surgical treatment, resulting in incomplete tumor removal or suboptimal deformity correction.…”
Section: Utilization: In What Context Are Eps Used?mentioning
confidence: 94%
“…Thirumala et al (2014) examined SEP performance in a large retrospective series of surgeries for idiopathic scoliosis. Kobayashi et al (2014) examined MEP performance during spine surgeries with diverse patient diagnoses. They recognized that the neurological status of the patient during a RSC is unknown, and the initial decline could be either a true or false positive.…”
Section: Causal Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamaki et al 4 reported that six patients experienced postoperative neurologic complications, and that, in these patients, the peak amplitudes of the SCEPs diminished to less than 50% of the control values. Recently, Kobayashi et al 5 recommended the designation of an alarm point at a 70% decrease in TcMEPs amplitude for routine spinal cord monitoring. In accordance with those reports, we usually conduct spinal surgery using TcMEPs with an alarm point of less than 30% of the amplitude of the control values.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some criteria exist, such as decreased amplitude by 50%, 70%, 80%, or even 88%. 11,[19][20][21] It was reported that the risk of MEP deterioration was higher in patients with preoperative spinal deficits than in normal patients. 11 Taher …”
Section: Deteriorated Signals and The Achievement Of The "Alarm Pointmentioning
confidence: 99%